The Combined Effect of Syzygium Polyanthum and Honey Decoction on Lowering Blood Pressure: A Pra Experimental Approach - Dwi Antara Nugraha; Paulus Subiyanto; Esa Roy Tama (PT.Mantaya Idea Batara, 2026)
Background: As of 2026, hypertension, often referred to as the